Efficacy and functionality of sugarcane original vinegar on mice - Zheng, Feng-Jin; Lin, Bo; Yang, Yu-Xia; Fang, Xiao-Chun; Verma, Krishan K.; Chen, Gan-Lin (Frontiers in Microbiology, 2023)
Due to their bioactive compounds and beneficial health effects, functional foods and plant-based natural medicine are widely consumed. Due to their bioactivities, which help to human body, vinegar is one of them. Sugarcane original vinegar (SOV) is a special vinegar made from sugarcane as raw material through biological fermentation processes. The objective of this research was to assess the effects of sugarcane original vinegar on growth performance, immune response, acute oral toxicity, bacterial reverse mutation, mammalian erythrocyte micronucleus, mouse spermatogonial chromosome aberration and mammalian bone marrow cell chromosome aberration changes and serum characteristics on mice. Distortion parameters were used to assess its safety, and at the same time, the functionality of SOV was monitored during experimentation. The results shows that the SOV has no damage and inhibitory effect on the bone marrow red blood cells of mice, and no mutagenic and distortion-inducing effects on the bone marrow cell chromosomes and spermatogonia chromosomes, it’s safe to eat. SOV can improve blood lipids and reduce blood lipid content. The research results provide on data basis for the intensive processing of sugarcane and the development of high-value SOV products. Sugarcane original vinegar has beneficial impact on the performance, immune response and chromosomal aberration. The production application influences the vinegar quality, and consequently, its health benefits.